An AIE-based bioprobe for differentiating the early and late stages of apoptosis mediated by H2O2. Issue 33 (5th August 2016) - Leung, Anakin C. S.; Zhao, Engui; Kwok, Ryan T. K.; Lam, Jacky W. Y.; Leung, Chris W. T.; Deng, Haiqin; Tang, Ben Zhong
Abstract : A bioprobe, TPE–Zn2 BDPA, with aggregation-induced emission characteristics was designed and synthesized to differentiate the early and late stages of apoptosis mediated by H2 O2 . Abstract : A bioprobe, TPE–Zn2 BDPA, with aggregation-induced emission characteristics was designed and synthesized to differentiate the early and late stages of apoptosis mediated by H2 O2 . TPE–Zn2 BDPA does not respond to healthy cells, but it selectively lights up the membrane of apopotic cells in both stages with brighter fluorescence in the late apoptotic stage.